Exploring Views about LARCs Among Parenting Rural Latinx Teenagers, Their Mothers, and Providers: Implications for Sexuality Education and Care. Issue 2 (3rd April 2019) - Ruiz, Yumary; Riciputi, Shaina; Guilamo-Ramos, Vincent; Alexander, Stewart C.
Abstract: While long-acting reversible contraception (LARC) reduces risk of repeat-births, use remains low among rural Latinx adolescent mothers. This qualitative study identified perspectives about factors that influence LARC use among this population. Participants were dyads of parenting Latinx adolescent daughters and their mothers ( n  = 9 dyads) and nurses ( n  = 17). Findings revealed themes specific to this vulnerable population including (a) distinct ways LARC characteristics fit into parenting teenagers' lives, (b) supportive health care climate toward LARCs, and (c) factors that inhibit LARC uptake. The study has implications for sexuality education that seeks to reduce repeat-births among this population.